Reaction to Price Changes and Aspiration Level Adjustments - Itzhak Gilboa; David Schmeidler (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1994)
We claim that preferences of economic agents cannot be assumed given; rather, they are partly determined by the process of trade in the market, by information about the latter and so forth. In other words, preferences determine actions which, in turn, determine preferences. Thus classical tools of analysis such as the neo-classical utility function and the demand curve should be viewed merely as first approximations, which are too simplistic for many purposes. Changing preferences are not restricted to such phenomena as addiction, advertisement and so forth. Rather, for any product a satisficing consumer has an aspiration level, which is subject to change. The consumer's preferences, as reflected in choice behavior, will also change once the aspiration level is adjusted. We illustrate these claims by analyzing two example concerning consumer reaction to price increases. We analyze the effect of aspiration level adjustments on the dynamic pattern of a single consumer's demand, and show that such adjustments generate predictions which do not conform to the neo-classical theory.
Keywords: 330